Developing a causal relationship model in business development That affect the excellence of public business organizations - et. al., Prumsub Wetsukum, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aimed to develop a causal relationship model in business development impacting the excellence of public business organizations in Thailand and to verify the consistency of the developed causal relationship model with the data. The research tool was an online questionnaire sample were 400 former business executives, public business organizations in Thailand. The statistics used for data analysis were structural equation models used to analyze causal relationships for Finding the path of the causal influence of variables consists of 5 areas: 1) Perception of safety of public business organizations in Thailand 2) Innovation in the development of public business organizations in Thailand 3) Image of public business organizations in Thailand 4) Trust in business management And 5) business development Public business organizations in Thailand The research found that the developed causal relationship model was very consistent with empirical data, the forecast coefficient of 0.98, indicating that the variables in The model can explain the variability of business development of public business organizations in Thailand 98% found that trust in the development of public business organizations in Thailand has the greatest influence on the development of public business executives. Of business operators in Thailand.